Comparative efficacy and hematologic safety of different dosages of JAK inhibitors in the treatment of myelofibrosis: a network meta-analysis - Chen, Ke; Zhang, Yanyu; Zou, Jixuan; Wang, Dehao; Yu, Xinyue; Sun, Yan; Li, Yumeng; Niu, Jicong; Chen, Yi; Zhao, Pei; Liu, Weiyi; Lv, Yan (Frontiers in Oncology, 2024)
BackgroundMyelofibrosis (MF) is a myeloproliferative neoplasm characterized by bone marrow fibrosis associated with substantial morbidity and mortality. The therapeutic landscape for MF has advanced with the development of Janus kinase inhibitors (JAKis) like ruxolitinib (RUX), fedratinib (FED), pacritinib (PAC), and momelotinib (MMB), aiming to alleviate symptoms and enhance patient comfort.MethodsA network meta-analysis was conducted to assess the efficacy and safety of eleven JAKi treatment regimens across nine randomized controlled trials (RCTs) with a total of 2340 participants. Outcomes were evaluated in terms of spleen volume reduction (SVR), total symptom score reduction (TSSR), hematological safety profiles, and overall survival (OS).ResultsRUX and MMB were superior in achieving SVR and TSSR, with significant dose-response relationships observed. PAC and MMB were associated with a decreased risk of grade 3/4 anemia and thrombocytopenia compared to other JAKis. However, no substantial benefits in OS were observed with newer JAKis compared to RUX. The poorer OS outcomes with certain PAC dosages were likely influenced by baseline patient characteristics, particularly severe cytopenias.ConclusionThe introduction of JAKis significantly changed the treatment of MF. This meta-analysis reaffirms the core role of RUX and positions MMB as a potentially powerful alternative for treating symptoms and reducing spleen size. Meanwhile, MMB and PAC have a positive effect on anemia in MF while FED is more tolerable for patients with thrombocytopenia. However, it should be noted that these results are influenced by baseline patient characteristics, particularly cytopenias, which affects both management and overall survival. Therefore, there is an urgent need for personalized dosing strategies to optimize the balance between efficacy and safety, with careful consideration of patient-specific factors.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023424179.